PELAKSANAAN KONSELING TANDA-TANDA BAHAYA KEHAMILAN MENGGUNAKAN BUKU KIA DI KELURAHAN TALANG JAMBE PALEMBANG TAHUN 2021 - Sri Emilda; Vera Yuanita (Jurnal Pengabdian Masyarakat Nusantara, 2022)
Although pregnant women have received the MCH handbook, one page of which contains knowledge about the danger signs in pregnancy, the knowledge of pregnant women about the danger signs in pregnancy is still lacking because educational factors are also considered to affect the ability of pregnant women to read and understand the contents of the MCH book. The implementation of counseling and counseling is intended so that participants who come during counseling know or understand the danger signs of pregnancy. Located in the Talang Jambe sub-district, Palembang with 10 counseling participants and has been given counseling and counseling materials about the danger signs of pregnancy using the MCH book, on Tuesday, March 16, 2021. The final outcome of this activity is that the participants are able to understand the signs dangers of pregnancy. The conclusion of this activity is that the counseling and counseling participants are able to understand the danger signs of pregnancy and the counseling activities are carried out smoothly.